Screening for hazardous alcohol use and dependence in psychiatric in-patients using the AUDIT questionnaire - Hulse, G.; Saunders, J.; Roydhouse, R.; Stockwell, Tim; Basso, M. (Taylor and Francis, 2000)
The Alcohol Use Disorders Identification Test (AUDIT) has been used to screen for hazardous and harmful alcohol consumption among general hospital populations but not in psychiatric patients. Using the AUDIT, we assessed alcohol use in patients with four major types of psychiatric disorder, namely mood, adjustment, anxiety and psychotic disorders. Nine hundred and ninety consecutive admissions to the psychiatric units of two hospitals during a 12-month period underwent assessment. In each diagnostic group a high proportion of patients was alcohol-dependent. Among those with mood disorders 25.4% of men were alcohol-dependent, compared with 16.3% of women, while 34.5% of men with anxiety disorder were alcohol-dependent compared with 25.0% of women. Both gender differences were statistically significant. The differences were even greater for adjustment disorder (44.4% vs. 14.5%) and psychosis (29.2% and 4.2%, respectively). More men than women with anxiety disorder were classified as hazardous (24.1% vs. 11.7%) or harmful drinkers (13.8% vs. 3.3%), but for the other diagnostic groupings the percentages in these drinking categories were more nearly similar. Thus, there is a high rate of excessive alcohol consumption in people with psychiatric disorders, especially males. Such individuals may be particularly vulnerable to complications of alcohol misuse such as suicide and exacerbation of their disorder. The potential for decreased severity of psychiatric symptoms and a reduction in the number of hospital admissions following cessation or reduction in alcohol consumption is considerable. The AUDIT is a simple screening device for investigating alcohol use and dependence, and offers a means of initiating intervention in this population.